Adsorption Experiment for Measuring the Atenolol Adsorbing Ability of Thermally Reduced Graphite Oxide - Ladan H. M. A; Buba A. D. A.; Umar M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
In this study, the microscopic and spectroscopic analysis of thermally reduced graphite oxide and testing its adsorbing ability from 50 to 400 0C was conducted. The samples were characterized by X-ray fluorescence (XRF), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), UV visible near infra-red and Fourier transforms (FTIR) spectroscopy to ascertain the crystalline nature, morphology, photo response, bonding and functional groups. The sample was tested for the removal of atenolol (ATL) in aqueous solutions by adsorption experiment. XRF analysis showed the presence of C, MgO, SiO2, and SrO at 15.0%, 4.35%, 25.14%, and 9.73% respectively. XRD spectra showed the crystalline forms and sharp diffraction peak. SEM analysis revealed reflective surface and impurity sites. The study has proved that the RGO is suitable for the removal of ATL at 60% and the graphite is effective in treating water contaminated with drugs for treating cardiovascular diseases. It is of high quality and suitable for exportation as a source of foreign exchange.